PENGARUH PEMBERIAN ROM AKTIF DAN PASIF TERHADAP PEMULIHAAN TONUS OTOT PADA PASIEN STROKE - Ida Misaroh (Nusantara Hasana Berdikari, 2022)
Stroke in Indonesia is 10.9% or an estimated 2,120,362 people. With the large number of cases, it is expected that Range of motion can have an effect on increasing muscle tone strength. Objective to review the effect of active and passive ROM on the recovery of muscle tone in stroke patients. Literature review with Analysis approach for data analysis used, namely, Thematic Analysis: Simplified approach. Researchers using databases such as Google Scholar, sqElsiver, Research Gate, and Pubmed found 30 studies in the literature review and were filtered into 7 that met the inclusion criteria for discussion. The effect of Range Of Motion on increasing muscle tone strength in stroke patients. Range Of Motion can be used as a non-pharmacological intervention.